Arithmetische Funktionen in Mengen der Werte von Polynome mit ganzzahligen Koeffizienten - Uždavinys, R. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Уждавинис. Арифметические функции на множествах значений целочисленных полиномовR. Uždavinys. Aritmetinės funkcijos polinomų su sveikais koeficientais reikšmių aibėse